Wood Anatomy and Fibre Quality of the Least Known Timbers Belong to Actinidiaceae from Indonesia - Ratih Damayanti; Listya Mustika Dewi (Wood Research Journal, 2019)
Wood anatomy of 417 genera and 86 families belong to the major, minor, and the lesser  known timbers of South- East Asia have been studied and described in 3 volumes of PROSEA books. This paper deals with timber species  of the least known timbers, which have  not been  treated in the above  mentioned  PROSEA books, i.e.:  Saurauia bracteosa, S. capitulata., and S. nudiflora from family Actinidiaceae.  The  objective  of this study was  to acquire  descriptions of their anatomical  features and evaluate  the quality of their fibres for pulp and paper manufacture. Samples were provided by Xylarium Bogoriense,   which were collected  from various  forest  areas   in  Indonesia.   Microscopic features  observed comprise all features those listed by IAWA Committee in 1989. Fibre quality was determined based  on their dimension and evaluated  according to quality classification developed  by FPRDC  Bogor. The results indicate  that identification of timber up to genera level is possible. Fibres of Saurauia spp.  fall into quality class  I, which  means   good  for pulp and paper. The descriptions of anatomical features were presented. Sauraria have  bright color, light yellow to light brown, fine texture, light, smooth to rather rough surface,  and make it suitable to substitute ramin (Gonystylus  spp.)